BIOPHYSICAL MODELING OF CARDIOVASCULAR ADAPTATION IN PATIENTS WITH ARTERIAL HYPERTENSION IN UZBEKISTAN (Modern American Journal of Medical and Health Sciences, 2026)
Cardiovascular adaptation represents a complex biophysical process reflecting the ability of the circulatory system to maintain functional stability under physiological and environmental stress. In regions characterized by specific climatic conditions and lifestyle patterns, adaptive mechanisms may undergo early functional alterations that remain undetected by conventional clinical assessment.